TEACHING WRITING DESCRIPTIVE PARAGRAPHS THROUGH CAREER EXPLORATION TECHNIQUE TO THE TENTH GRADE STUDENTS OF STATE SENIOR HIGH SCHOOL 5 OF PALEMBANG - Neta Desti Kurniati (Universitas PGRI Palembang, 2020)
Abstract: Career exploration technique is a technique by guiding the students to expend their idea, make decision, and explore the information about something that will be developed into written. Therefore, the main objectives of this study was to investigate the significant difference between students’ writing achievement of the tenth grade students taught through career exploration technique and those taught through conventional teaching method of State Senior High School 5 of Palembang. This study applied a quasi-experimental design. The population in this study was all the tenth grade students of State Senior High School 5 of Palembang in academic year of 2019/2020 with 357 students. The sample was 70 students. They were 36 students as experimental group from Class X.IPA.1 and 34 students as control group from Class X.IPA.2 taken by using purposive sampling. The data were collected by using a written test, pre-test, post- test and analyzed by using paired sample t-test and independent sample t-test to compare the improvement between both groups. The result of the study showed that the students’ pretest average score in the experimental group was 78.25 and in post-test it was 84.16. While, the students’ pre-test in the control group was 78.88 and in the post-test was 78.88. The value of t- obtained (4.385) was higher than the value t-table (1.671), at the significant level 0.05 in one tailed with df=68. Since the value of t-obtained was higher than the value of t-table (4.85 > 1.684), consequently the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It means that there was significant difference on teaching writing descriptive paragraphs through Career Exploration Technique to the tenth grade students of State Senior High School 5 of Palembang and those who are not.